Pengembangan Buku Nonteks Biologi SMA Kelas X Berbasis Pengetahuan Etnobotani di Kabupaten Situbondo - Afrida Tul Rofi'ah; Sulifah Aprilya Hariani; Pujiastuti Pujiastuti (Universitas Lampung, 2021)
This study aims to produce non-textbooks based on ethnobotany in Situbondo district as a source of quality student learning with a valid, practical, and effective nature. The research used the Borg and Gall development model which consisted of 5 stages according to research needs. The research subjects were students from two class X MIPA at SMAN 1 Panarukan. Non-text books are validated by material expert validators, development experts, media experts, and linguists. The results of quantitative data analysis that have been validated by the validator with an average book value percentage of 85.75% are included in the eligibility criteria as very valid. The cloze test procedure results obtained an average percentage of 80.3% which is in the easy category. The average result of the N-Gain value is 0.58 which is included in the moderate effectiveness category. Non-text books that have been developed have good quality effectiveness, practicality, and readability to be used in classroom learning activities, especially on Kingdom Plantae material.Penelitian ini bertujuan untuk menghasilkan buku nonteks berbasis etnobotani kabupaten Situbondo sebagai sumber belajar siswa yang berkualitas dan bersiffat valid, praktis, dan efektif. Penelitian menggunakan model pengembangan Borg and Gall yang terdiri dari 5 tahapan sesuai kebutuhan penelitian. Subjek penelitian adalah siswa dari dua kelas X MIPA di SMAN 1 Panarukan. Buku nonteks divalidasi oleh validator ahli materi, ahli pengembangan, ahli media, dan ahli Bahasa. Hasil analisis data kuantitatif yang telah divalidasi oleh validator dengan rata-rata persentase nilai buku 85,75% termasuk ke dalam kriteria kelayakan sangat valid. Hasil uji rumpang atau Cloze Test Procedure diperoleh rata-rata persentase sebesar 80,3% yang termasuk kategori mudah. Hasil rata-rata nilai N-Gain adalah 0,58 yang termasuk kategori efektivitas yang sedang. Buku nonteks yang telah dikembangkan memiliki kualitas efektivitas, kepraktisan, dan keterbacaan yang baik untuk digunakan dalam kegiatan pembelajaran di kelas khususnya pada materi Kingdom Plantae. Kata kunci: Sumber belajar, buku nonteks, etnobotani, validasi DOI: http://dx.doi.org/10.23960/jbt.v9i2.22319